Esophageal fistula after definitive concurrent chemotherapy and intensity modulated radiotherapy for esophageal squamous cell carcinoma. - Tzu-Hui Pao (Public Library of Science (PLoS), 2021)
Background The literature regarding esophageal fistula after definitive concurrent chemotherapy and intensity modulated radiotherapy (IMRT) for esophageal squamous cell carcinoma (ESCC) remains lacking. We aimed to investigate the risk factors of esophageal fistula among ESCC patients undergoing definitive concurrent chemoradiotherapy (CCRT) via IMRT technique. Methods A total of 129 consecutive ESCC patients receiving definitive CCRT with IMRT between 2008 and 2018 were reviewed. The cumulative incidence of esophageal fistula and survival of patients were estimated by the Kaplan-Meier method and compared between groups by the log-rank test. The risk factors of esophageal fistula were determined with multivariate Cox proportional hazards regression analysis. Results Median follow-up was 14.9 months (IQR, 7.0-28.8). Esophageal perforation was identified in 20 (15.5%) patients, resulting in esophago-pleural fistula in nine, esophago-tracheal fistula in seven, broncho-esophageal fistula in two, and aorto-esophageal fistula in two patients. The median interval from IMRT to the occurrence of esophageal fistula was 4.4 months (IQR, 3.3-10.1). Patients with esophageal fistula had an inferior median overall survival (10.0 vs. 17.2 months, p = 0.0096). T4 (HR, 3.776; 95% CI, 1.383-10.308; p = 0.010) and esophageal stenosis (HR, 2.601; 95% CI, 1.053-6.428; p = 0.038) at baseline were the independent risk factors for esophageal fistula. The cumulative incidence of esophageal fistula was higher in patients with T4 (p = 0.018) and pre-treatment esophageal stenosis (p = 0.045). There was a trend toward better survival after esophageal fistula among patients receiving repair or stenting for the fistula than those only undergoing conservative treatments (median survival, 5.9 vs. 0.9 months, p = 0.058). Conclusions T4 and esophageal stenosis at baseline independently increased the risk of esophageal fistula in ESCC treated by definitive CCRT with IMRT. There existed a trend toward improved survival after the fistula among patients receiving repair or stenting for esophageal perforation.